Estudo dos acoplamentos magnéticos em nanoestruturas CoFe2O4@CoFe2 dispersas em matriz de Ag - Pinheiro, Antônia Veruska Benevides (2020)
Using the coprecipitation method, samples (precursors) of the CoFe2O4-Ag nanocomposite were synthesized, varying the concentration of CoFe2O4. These samples were subjected to thermal reduction, under H2 atmosphere at 350 ◦C, for different time intervals in order to obtain a core-shell nanostructure of CoFe2O4@CoFe2 dispersed in the Ag matrix. Through X-ray diffractometry, it was observed the phases CoFe2O4, CoFe2 and Ag„ where the peak of CoFe2 (shell) becomes more evident for samples reduced for a longer time. Rietveld refinements provide values for the size of CoFe2O4 nanoparticles (core) which decrease size with the increase in the reduction time, from 30 to 90 minutes. This decrease was also observed in Transmission Electron Microscopy images, and is around 0,5 nm. Meanwhile, the shell thickness (δCF ) changes from 2,5 nm to 3 nm between samples with a lower concentration of CoFe2O4 reduced by 30 and 90 minutes. The nanoparticles of Ag, in the precursor samples, have diameters of 11 nm, but this value increases to ≈ 15 - 20 nm after the heat treatment. Magnetization measurements, at 300 K, reveal a decrease in the coercive field (Hc) as δCF increases, and the behavior of the curves suggests an exchange spring coupling. A phenomenological model was developed to describe the behavior of magnetic interactions in relation to the distance between the core shell nanoparticles, Dnc, based on the analysis of Henkel and δm plots which are obtained through the relationship between the remaining reverse and direct magnetizations. For small Dnc distances, there is a greater contribution of dipolar interactions. When Dnc increases, the exchange interactions are more pronounced, as the contribution due to coupling at the core-shell interface is evidenced. Magnetization measurements as a function of the field in 4 K by zero field cooling and field cooling under a 1 T cooling field exhibit a horizontal shift in the curves, which can be attributed to freezing spins at the core-shell interface. It was found that the field of exchange bias (HEB) in samples with lesser δCF is approximately double that presented in samples with thicker δCF . This increase in HEB is related to the ratio of the surface area on one disordered layer to the volume of the ferromagnetic layer.